2016
DOI: 10.3390/molecules21030166
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing and Development of Genic SSR Markers of an Endangered Chinese Endemic Genus Dipteronia Oliver (Aceraceae)

Abstract: Dipteronia Oliver (Aceraceae) is an endangered Chinese endemic genus consisting of two living species, Dipteronia sinensis and Dipteronia dyeriana. However, studies on the population genetics and evolutionary analyses of Dipteronia have been hindered by limited genomic resources and genetic markers. Here, the generation, de novo assembly and annotation of transcriptome datasets, and a large set of microsatellite or simple sequence repeat (SSR) markers derived from Dipteronia have been described. After Illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 68 publications
2
26
0
Order By: Relevance
“…The new DNA sequencing methods provide rapid screening and development of microsatellite loci. Several studies point to a high number of loci identified from next-generation sequencing [23][24][25], thus facilitating the development of new markers and their use in population genetic studies. In this work, more than 8.5 million pairs of reads were generated in a single run, from which it was possible to identify more than 50,000 dinucleotide loci, 24 trinucleotides, 9 tetranucleotides, 10 pentanucleotides and 5 hexanucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…The new DNA sequencing methods provide rapid screening and development of microsatellite loci. Several studies point to a high number of loci identified from next-generation sequencing [23][24][25], thus facilitating the development of new markers and their use in population genetic studies. In this work, more than 8.5 million pairs of reads were generated in a single run, from which it was possible to identify more than 50,000 dinucleotide loci, 24 trinucleotides, 9 tetranucleotides, 10 pentanucleotides and 5 hexanucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…Two transcriptome datasets (SRR2127986/SRR2127991) from a previous study (Zhou et al, 2016 ) were used for the present comparative transcriptome analysis. Before assembly, the raw reads were filtered to obtain high-quality clean reads by removing adapters, low-quality sequences (reads with unknown bases “N”), and reads with more than 20% low-quality bases (quality value ≤ 10).…”
Section: Methodsmentioning
confidence: 99%
“…[19], Dipteronia spp . [20], Taxodium ‘zhongshansa’ [21], E . ulmoides [12], Pinus koraiensis [22], and Cunninghamia lanceolata [23]; however, to date, they have not been reported in S .…”
Section: Introductionmentioning
confidence: 99%